The talk of Coyote Canyon [large type] - Novak, Brenda (Novak, Brenda. Coyote Canyon, 2023)
With her piercings, tattoos and spiky blond hair, Ellen Truesdale doesn't quite fit in with the other folks in Coyote Canyon--and that's just fine with her. She's only here to put her father out of business, as payback for abandoning her when she was young. Or is she more interested in finally proving that she was worth keeping? Either way, she's struggling to keep her rival well-drilling company afloat. And being a single woman in a male-dominated field has started to take a toll. So when Hendrix Durrant steps in to help, Ellen has no choice but to let him--even though he happens to be her father's business partner and therefore her enemy. But the closer she works with him, the more she sees what she's been missing...in life and love. And once she lets go of her anger long enough to learn the truth about her past, she might just find the family she's always wanted.